2021
DOI: 10.3389/fpsyg.2021.752623
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve as a Protective Factor of Mental Health in Middle-Aged Adults Affected by Chronic Pain

Abstract: Chronic pain is associated with worse mental health and cognitive impairment, which can be a cause or a consequence of brain structure and function alterations, e.g., maladaptive plasticity, antinociceptive system dysregulation. Cognitive reserve reflects the effectiveness of the internal connections of the brain and it has been shown to be a protective factor in brain damage, slowing cognitive aging or reducing the risk of mental health disorders. The current study explored the impact of chronic pain on psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…RNT has been associated with lower subjective cognitive functioning and higher memory complaints among healthy older adults ( Schlosser et al, 2020 ), and hence the 12-item PROMIS Cognitive Abilities and Cognitive Concerns Scales was administered to measure subjective perceptions of memory function, attention and planning ( Fieo et al, 2016 ), as explained elsewhere ( Delgado-Gallén et al, 2021 ). The 5-point Likert scale was reversed so that higher scores meant greater cognitive complaints.…”
Section: Methodsmentioning
confidence: 99%
“…RNT has been associated with lower subjective cognitive functioning and higher memory complaints among healthy older adults ( Schlosser et al, 2020 ), and hence the 12-item PROMIS Cognitive Abilities and Cognitive Concerns Scales was administered to measure subjective perceptions of memory function, attention and planning ( Fieo et al, 2016 ), as explained elsewhere ( Delgado-Gallén et al, 2021 ). The 5-point Likert scale was reversed so that higher scores meant greater cognitive complaints.…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive model for understanding migraine pain should include not only the extensively studied risk factors and brain injuries or disruptions, but also the protective factors (18). In this perspective, Cognitive Reserve (CR) could potentially play a crucial role.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies on chronic pain syndromes have shown a negative correlation between pain perception, anxiety, and other mental factors with CR (22,23), lending further support to the literature suggesting an integrated emotional-cognitive processing. In particular, a study conducted by Delgado and colleagues found that CR played a moderating role in the relationship between pain intensity and mental health (18), suggesting that CR may be a useful tool with a great potential in advancing the assessment and treatment of chronic pain. Indeed, the efficiency of brain networks is greater in individuals with high CR, and may act as a compensatory mechanism while coping with the disease (12).…”
Section: Introductionmentioning
confidence: 99%
“…The research topic of cognitive reserve in cognitive decline is quite timely, and the benefits of reserve for cognition in older adults have been demonstrated many times, highlighting an association with the dementia phenotype [8][9][10]. This evidence would justify the empirical observation that, in some cases, the levels of brain pathology do not match with clinical symptoms [11].…”
Section: Introductionmentioning
confidence: 99%